Apparel Shopping Orientation of Urban Indians : A Study on Kolkata - Goswami, Paromita (Indian Journal of Marketing, 2007)
Apparel trade has immense potential in India in terms of increased consumer spend, export potential as well as branding opportunity. In this context, this paper takes a look at the shopping orientation of urban Indians with the help of a study on Kolkata in order to segment the shoppers on the basis of psychographic as well as demographic dimensions. Kolkata being a cosmopolitan city with residents of different states speaking different languages and belonging to different sub-cultures, the study would help explore the apparel shopping behavior of urban Indians in general. It also discerns the difference in the shopping orientations of brand-loyal and non-brand loyal customers. Accordingly, the shoppers are divided into four categories, namely, utilitarian shoppers, conservative shoppers, hedonic shoppers and socializing shoppers. For this purpose, multivariate techniques of factor analysis, cluster analysis and discriminant analysis are used. In terms of frequency of purchase the hedonic shoppers are the best target group among the four segments of shoppers identified. As far as brand loyalty is concerned, it was found that the brand loyal consumers prefer stores near their homes and work places, realize the importance of paying higher price to get better quality and look for more variety and quality in stores while purchasing apparel.